ฤทธิ์ยับยั้งจุลินทรีย์ของสารสกัดจากสมุนไพรไทย - ทศพร ลีลา (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This study evaluated the antimicrobial actiivities of crude extracts of traditional Thai herbs i.e. Piper betle Linn, Boesenbergia pundurata, Alpinia galangal, Coccinia indica and Quercus infectoria galls against both gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) by Disc diffusion method using solvents of different polarities. The results showed that the methanolic extracts can inhibit all the tested microbial strains. The crude extracts of Q. infectoria galls exhibited the highest antimicrobial activity. The average clear zone of the inhibition of Q. infectoria galls ranged from 10.3 to 25.3 mm. The minimum inhibition concentration values of the extracts ranged from 0.3125 mg/L to 1.250 mg/L whereas the minimum bactericidal concentration values ranged from 0.625 mg/L to 1.250 mg/L. The combinations of two or three herbal extracts were tested in three microbial strains. The combination of the exacts significantly enhanced their activity compared with a single extract. The antimicrobial compounds in the extracts of Q. infectoria galls were identified as phenolic compounds of 14.8 % by weight. The optimum conditions for the extraction were found at 24 h extraction time, room temperature, particle size of 75 μm, solvent to solid ratio of 5:1 and using methanol as solvent. Scanning electron microscopy illustrated a complete loss of cell surface and morphological changes of all the test microbial strains by the extracts of Q. infectoria galls.